Methods for determining the geographic azimuth by solar observations - Santos Rodríguez, Ricardo (2012)
The present research had like specific objective to develop a methodology that, having a solid theoretical sustenance, allows to determinate the direction o fan alignment with a minimum precision that serves as a base for all civil infrastructures Project in urban and rural spaces. For which after a specialized bibliographical revision and of the ordering of concepts, the analytical processes and the evaluation of the results allowed the exposition in direct form the determination of the geographic azimuth by solar observations, being obtained with this form a precision of the order of ± 30´´.